(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
About a recent formal Note of the Holy See on the legal doctrine of ’discovery’. Towards a revirement of the traditional orientation? ABSTRACT: This article intends to conduct an brief analysis on the significance of some recent pronouncements of the Catholic Church that question the foundations of the traditional doctrine of discovery, which has been forged by the colonial powers since the sixteenth century and has found particular expression in the nineteenth-century legislation and jurisprudence of the courts of several countries, including the United States and Canada. SOMMARIO: 1. Gli esordi del colonialismo nel ‘Nuovo Mondo’ e il ruolo della Chiesa cattolica - 2. Presupposti teorici e ricadute della doctrine of discovery sulla giurisprudenza circa gli American Indians. Il sistema canadese delle Residential Schools - 3. La Nota formale a cura del Dicastero per la Cultura e l’Educazione e per il Servizio dello Sviluppo Umano Integrale del 30 marzo 2023 – 4. Prime reazioni delle Conferenze episcopali della regione a margine del pronunciamento curiale - 5. Aspetti internazionali del problema e rilievi conclusivi